Evidências do envolvimento de citocinas pró-inflamatórias no comportamento do tipo depressivo durante a retirada do etanol em camundongos - Fraga Junior, Eguiberto Bernardes (2019)
Epidemiological studies have shown that alcoholism and depression occur together, and that in both disorders there is elevation in the expression of proinflammatory cytokines. These changes remain after the suspension of chronic alcohol consumption and contribute to the symptomatology characteristic of abstinence. The present study aimed to evaluate whether the positive regulation of cytokines during alcohol withdrawal is associated with the behavior of the depressive type in this period. Swiss albino mice treated with alcohol were used for 14 days followed by 5 days of abstinence. In this model, the abstemious animals presented elevation of tumor necrosis factor alpha (TNF-α) in the hippocampus and striatum, interleukin-one beta (IL-1β) in the hippocampus and interleukin six (IL-6) in the cortex and hippocampus; accompanied by increased immobility time in the tail suspension test (TSC) and in the forced swimming test (TNF). The use of anti-inflammatory agent (nimesulide) reversed depressant-type behavior in abstinent animals and the effect of chronic alcohol exposure on levels of TNF-α in the hippocampus and striatum, IL-1β in the hippocampus, and IL-6 in the cortex, hippocampus and striatum. Vilazodone (atypical antidepressant) decreased the time of immobility in TSC and TNF in abstinent animals and prevented the increase of TNF-α in the hippocampus, IL-1β in the hippocampus, and IL-6 in the striatum. These data support the involvement of proinflammatory cytokines in the abstinence period and its relation to the behavior of the depressive type observed in alcoholic detoxification.